Cost Analysis of the Fukuoka Method Landfill System in North Kolaka Regency, Southeast Sulawesi, Indonesia - Rahim, Irwan Ridwan; Jamaluddin, Abdulrahman (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Most waste disposal sites in developing country are still using open dumping and open burning. However, in developing countries, there are a lot of economic and technical problems with high level landfill technologies of first world countries, which makeimplementation of improvement is not feasible. Therefore, there is a significant need for transfer of landfill technology that is considered simpler, low cost, and that can be maintained locally. A method that provides these standards, which has recently gathered attention is the Fukuoka Method (semi-aerobic landfill).By life cycle cost analysis method, with the lifespan of the landfill is 20 years and an estimated volume of586,789 m3 (469,431tons), the required capital investment was about US$296,739 (natural clay liner)and US$463,406 (syntheticliner) or about US$0.63 and US$0.99/ton of waste. It is also calculated thatthe total cost of operation was about US$3,187,728 or US$6.79/ton of waste. The closure cost of the landfill was estimated to beUS$278,116 or US$0.59/ton of waste.